Bond strength of composite resin containing biomaterial S-PRG to eroded dentin - Alessandra Sanchez Coelho Lourenço; Ana Paula Almeida Ayres; Taís Fonseca Mantilla; Marcelo Giannini; Patricia Moreira de Freitas (Universidade Estadual de Campinas, 2017)
Aim: To evaluate the bond strength of composite resin containing or not biomaterial (S-PRG) to sound/eroded dentine. Methods: Occlusal dentin of 30 human molars (n=15) had half of its surface kept uneroded, while on the other half an erosive lesion was produced by cycling in citric acid (pH 2.3) and supersaturated solution (pH 7.0). On both eroded (ED) and non-eroded (SD) substrates, two restorative systems (containing or not S-PRG) were tested. Composite resin cylinders were built and, after storage in water (24h), were submitted to bond strength test. The analysis of the fracture pattern was performed under an optical microscope (40x). The obtained values of bond strength (MPa) were submitted to ANOVA (two factors) and Tukey multiple comparisons tests (p<0.05). Results: According to the results, there was difference between substrates (<0.001) and restorative materials (p=0.002) evaluated. For the microtensile bond strength, the values obtained were: SDNB (47.6±12.2 MPa), SDWB (34.1±15.8 MPa), EDNB (31.1±8.3 MPa) and EDWB (15.5±13.6 MPa), revealing a statistically significant difference in the evaluated substrates and restorative materials. Conclusion: Bond strength of eroded substrate is inferior to the sound substrate and the restorative system containing S-PRG biomaterial influences negatively the results of bonding to sound/eroded dentin.